Reimagining discipleship pathways for pluralist societies: Faith development theory and the theology of Christian formation in conversation - Seager, James (Journal of Pentecostal and charismatic Christianity, 2023)
This paper uses the pastoral cycle to facilitate a dialogue between Faith Development Theory (FDT) and the theology of Christian formation concerning the practice of ‘discipleship pathways’ within pluralist contexts. Firstly, the general experience of pathways in local churches is elucidated by synthesizing three distinct examples of pathways and noting how pluralist contexts challenge it. FDT is then explored, and its points of divergence with pathways are noted. Following this, the reflection presents points of correlation between FDT and the theology of Christian formation, and argues that disciples mature primarily through encountering the Spirit via spiritual disciplines, which results in their inner person being aligned with God’s will, and being motivated to incarnate the fullness of Jesus among people with differing moral and religious values. From this, alterations to pathways are suggested that focus on the principles of ‘spiritual direction’, which better connect pathways with disciples who inhabit pluralist societies.